2021
DOI: 10.3390/ma14041034
|View full text |Cite
|
Sign up to set email alerts
|

FeSiCr Alloy Powder to Carbonyl Iron Powder Mixing Ratio Effects on the Magnetic Properties of the Iron-Based Alloy Powder Cores Prepared Using Screen Printing

Abstract: A screen printing process was used to substitute dry molding to solve the uneven compaction problem in the coil center column during molding in this study. FeSiCr alloy powders (FSC) with a large particle size were mixed with fine spherical carbonyl iron powder to increase the compaction density. FSC to carbonyl iron powder (CIP) mixing ratio effects on magnetic paste rheological behaviors and magnetic properties of the molding coil prepared using screen printing were investigated. A magnetic paste with the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As the amount of carbonyl iron powder added increased, the relative density decreased. This is due to carbonyl iron powder exceeding the amorphous FeSiCrB alloy powder’s interstice volume and widening interparticle distances, and the large amorphous FeSiCrB alloy powder cannot fill the small interstices formed by the small-sized carbonyl iron powders [ 18 ]. Due to the large plastic deformation of carbonyl iron powders during compaction, 0K10C-A has a higher relative density than 10K0C-A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the amount of carbonyl iron powder added increased, the relative density decreased. This is due to carbonyl iron powder exceeding the amorphous FeSiCrB alloy powder’s interstice volume and widening interparticle distances, and the large amorphous FeSiCrB alloy powder cannot fill the small interstices formed by the small-sized carbonyl iron powders [ 18 ]. Due to the large plastic deformation of carbonyl iron powders during compaction, 0K10C-A has a higher relative density than 10K0C-A.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonyl iron powder (CIP) has a number of advantages, including a low cost and high saturation magnetization [ 17 ]. Hsiang et al [ 18 ] reported that by incorporating CIP into FeSiCr alloy powders, the compaction density of the molding coils could be increased due to the large plastic deformation during pressing, and thus the inductance could be increased. In this study, the silicone resin was used as the organic binder for molding power inductors.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonyl iron powder (CIP) has many benefits, including low cost and high saturation magnetization [11]. According to Hsiang et al [12,13], introducing CIP into FeSiCr alloy powders and amorphous alloy powder can increase the compaction density of molding coils due to significant plastic deformation during pressing, resulting in increased inductance. However, a detailed evaluation of the magnetic characteristics of soft magnetic composites made with individual and binary mixes of carbonyl iron powder, FeSiCr alloy powder, and nanocrystalline alloy powder has yet to be performed.…”
Section: Introductionmentioning
confidence: 99%